The Bible, ecumenism, spirituality. In search of Christian unity - Sawa, Przemysław (The Bible as a meeting place for Christian denominations, 2022)
The search for unity among Christians is still relevant. On the one hand, this stems from the desire for unity expressed by Jesus during the prayer in the Upper Room, and on the other hand, it is about the natural need to be together with others and the credibility of the Christian message. It is not possible to move forward on the road to unity without respect, friendly coexistence or even action. The basis, however, is that every Christian builds a personal relationship with Jesus through the Word of God and a deep and healthy spiritual life. Therefore, contemporary ecumenism must be more spiritual and relational, with a courageous exchange of spiritual gifts and a common fulfillment of the mission entrusted by Christ. This adventure begins in what unites. Undoubtedly, this is the Word of God and the profession of faith in Jesus Christ.